Description of a new species of Stauropathes (Anthozoa, Antipatharia, Schizopathidae) from Puerto Rico - Jeremy Horowitz; Mina Barajas; Luke J. McCartin; Samuel A. Vohsen; Santiago Herrera (ZooKeys)
A new species of black coral, Stauropathes monopinnata sp. nov., represented by two specimens collected 738 m and 1604 m deep off Puerto Rico and Hawaii, respectively, is recognized in the family Schizopathidae. The new species is characterized by a monopodial, unbranched corallum; simple, suboppositely arranged pinnules in two anterolateral rows along the stem with nearly 90° distal angles, spaced 12–17 mm apart in a row, and with smooth and triangular spines 0.05–0.08 mm tall; and polyps 4–9 mm in transverse diameter. A phylogeny composed of 90 taxa representing species in Schizopathidae and Cladopathidae (rooted in Cladopathidae) was reconstructed from 794 nuclear loci to show their systematic relationships. Herein, we provide morphological and molecular evidence to show that this new species is distinct from other species in the genus Stauropathes.